Rightsizing Brazil's Public-Sector Wage Bill - Karpowicz, Izabela (IMF Working Papers; Working Paper ;, 2018)
Brazil's public-sector wage bill is comparatively high. It grows inertially and competes with other spending. Rightsizing the wage bill could stimulate administrative efficiency and bring more equity into a system where public employees earn more than private in comparable professions. Most importantly, however, a reform is necessary to comply with the Federal government expenditure ceiling and the subnational fiscal responsibility rules. A reform should thus encompass all government levels, and all careers, and should aim to achieve a real decrease in salaries and lower employment. In the medium term, a review of the compensation structure should rationalize the multitude if wage grids, merge allowances into the base wage, and align public sector compensation to private wages in low-skilled professions.